Phage cocktail SalmoFREE® reduces Salmonella on a commercial broiler farm. (9th May 2019) - Clavijo, V; Baquero, D; Hernandez, S; Farfan, J C; Arias, J; Arévalo, A; Donado-Godoy, P; Vives-Flores, M
ABSTRACT: According to the World Health Organization, Salmonella is one of the most important zoonotic foodborne pathogens. Poultry products are thought to be the main source of Salmonella, which means that it is necessary to control Salmonella at the pre-harvest stage. Bacteriophages, acting as host-specific parasites of bacterial cells, represent one of the alternatives to antibiotics that can contribute to food safety and security. The present study evaluated the effectiveness of the bacteriophage cocktail SalmoFREE ® to control Salmonella on a commercial broiler farm. We assessed the relationship between the use of SalmoFREE ® and productivity parameters (feed conversion, weight gain, homogeneity). Two field trials (trial 1 n = 34, 986; trial 2 n = 34, 680) were carried out under commercial rearing conditions on a Colombian broiler farm with a record of Salmonella presence. Each trial comprised 2 control chicken houses and 2 experimental ones. SalmoFREE ® and a control suspension were delivered in the drinking water at 3 time points in the production cycle, and the presence of Salmonella was assessed in cloacal swabs the day before and after the treatments. Results revealed that SalmoFREE ® controls the incidence of Salmonella and does not affect the animals nor the production parameters, demonstrating its efficacy and innocuity at the production scale. We detected phage-specific genes in samples of total DNA extracted from ceca after the treatment with SalmoFREE ®, and tested for the appearance of cocktail-resistant Salmonella, which showed to be an uncommon event. These results contribute relevant information to the adoption of phage therapy as an alternative to growth-promoter antibiotics on poultry farms.